1994
DOI: 10.1111/j.1365-2885.1994.tb00244.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of the action of flunixin meglumine and tolfenamic acid on prostaglandin E2 synthesis in bovine inflammatory exudate

Abstract: An acute non-immune inflammation model was used to compare the action of two non-steroidal anti-inflammatory drugs, flunixin meglumine and tolfenamic acid, on prostaglandin E2 (PGE2) synthesis in bovine inflammatory exudate. The tissue cage model used involves subcutaneous implantation of polypropylene cages and subsequent stimulation by carrageenan injection of the granulation tissue which develops within the cage. Twelve calves were randomly assigned to three groups receiving placebo, flunixin meglumine and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…As expected, flunixin meglumine had no influence on the lipoxygenase pathway. This confirmed the in-vivo results of Espinasse et al (1994).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…As expected, flunixin meglumine had no influence on the lipoxygenase pathway. This confirmed the in-vivo results of Espinasse et al (1994).…”
Section: Discussionsupporting
confidence: 89%
“…After 1 h, a slightly enhanced PGE 2 concentration was obvious. Compared with the in-vivo results of Espinasse et al (1994), where the inhibition set in 30 min after administration of flunixin, our model took a longer time. The reason for this is because in contrast to the in-vivo experiments where the eicosanoids were measured subcutaneously, in our in-vitro model flunixin had to diffuse into the epidermis and dermis as the loci of inflammation.…”
Section: Discussionmentioning
confidence: 92%
“…This is obviously due to biological variability. Espinasse et al (15) showed a comparable variability in bovine exudate in vivo. In addition, the variability of the PGE 2 concentration may also have been caused by the slightly differing depth of the microdialysis membrane.…”
Section: Discussionmentioning
confidence: 89%
“…These findings are consistent with the antipyretic, anti‐inflammatory and antitoxic properties of flunixin. In cattle, flunixin reduces the plasma concentration of thromboxane B 2 and prostaglandin E 2 and thus, is effective against inflammatory response to endotoxins (Anderson & Hunt, 1989; Espinasse et al ., 1994; Odensvik & Magnusson, 1996).…”
Section: Proportions Of Cows With Complete Uterine Involution and Camentioning
confidence: 99%